Strain echocardiographic assessment of left atrial function predicts recurrence of atrial fibrillation. (27th July 2015) - Sarvari, Sebastian I.; Haugaa, Kristina H.; Stokke, Thomas M.; Ansari, Hamza Z.; Leren, Ida S.; Hegbom, Finn; Smiseth, Otto A.; Edvardsen, Thor
Abstract: Aims: We evaluated if a dispersed left atrial (LA) contraction pattern was related to atrial fibrillation (AF) in patients with normal left ventricular (LV) function, and normal or mildly enlarged left atrium. Methods and results: We included 61 patients with paroxysmal AF (PAF). Of these, 30 had not while 31 had recurrence of AF after radiofrequency ablation (RFA). Twenty healthy individuals were included for comparison. Echocardiography was performed in patients in sinus rhythm the day before RFA. LA volume was calculated. Peak negative longitudinal strain was assessed in 18 LA segments during atrial systole. Contraction duration in 18 LA segments was measured as the time from peak of the P wave on electrocardiogram to maximum myocardial shortening in each segment. The standard deviation of contraction durations was defined as LA mechanical dispersion (LA MD). LA size was rather preserved in patients with PAF (LA volume 25 ± 10 mL/m 2 ). LA MD was more pronounced in patients with recurrence of AF after RFA compared with those without recurrence and controls (38 ± 14 ms vs. 30 ± 12 ms vs. 16 ± 8 ms, both P < 0.001). LA MD was a predictor of PAF [OR 7.84 (95%CI 2.15–28.7), P < 0.01, per 10 ms increase] adjusted for age, LA volume, e', and LA function. LA function by strain was reduced in both patients with and without recurrent AF after RFA compared with controls (−14 ± 4% vs. −16 ± 3% vs. −19 ± 2%, both P < 0.05). Conclusion: LA MD was pronounced, and LA deformation was reduced in patients with PAF with apparently normal LV structure and function, and normal or mildly enlarged LA. LA MD may be useful as a predictor of AF recurrence after RFA.